ANALISIS KESULITAN LITERASI MEMBACA DAN PEMAHAMAN BACAAN PADA SISWA KELAS II SEKOLAH DASAR (STUDI KASUS DI SDN LAREN 01) - Warkonah; Decky Avrilianda; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy is one of the basic skills that elementary school students must have, especially in the early grades. However, in practice, many students still experience difficulties in understanding simple reading. This study aims to analyze the reading literacy skills of second-grade students at SDN Laren 01 and identify factors that influence their low reading comprehension skills. This study used a qualitative descriptive approach with 21 second-grade students as subjects. Data collection techniques were carried out through observation, reading tests, and interviews with class teachers. The results showed that 5 students were not yet fluent readers, 12 students were able to read but did not understand the content of the reading well, and only 4 students were able to read and understand the content of the reading. These findings indicate that more than 50% of students still experience difficulties in understanding simple reading. Factors that influence students' low literacy skills include limited vocabulary, low reading habits, and reading learning strategies that still focus on reading fluency. Therefore, more interactive and contextual literacy learning strategies are needed to improve elementary school students' reading comprehension skills